Hardware development of electrical capacitance tomography for imaging a mixture of water and oil - Mohamad, Elmy Johana; Mohd Yunus, Fazlul Rahman; Abdul Rahim, Ruzairi; Chan, Kok Seong (Penerbit UTM Press, 2011)
This paper proposes the process of investigating the changes of capacitance value due to the changes of permittivity distribution of a different dielectric materials such as water and oil in a conveying pipeline using twelve externally Electrical Capacitance Tomography (ECT) sensor. Electrical capacitance tomography system is a system which can be used for imaging industrial multi-component processes involving non-conducting fluids in pipeline. Therefore, in this research, a 12 electrodes electrical capacitance tomography system is developed. This system can provide more data for processing to obtain more precise images of the pipeline. In order to reduce the noise in the system, on-plate signal conditioning board is applied in this research to eliminate certain noise source from the analogue transmission line. Then, various of ac capacitance measuring circuits has been developed in terms of performance and sensitivity to achieve low noise level, wide dynamic range and high immunity stray capacitance to suits the appropriate design for system development. The signal produced by the detection circuit is digitized by using multiplexing circuit, ADC circuit and buffering so that the transferring data is suitable for pc interface. A graphic user interface (GUI) is developed with visible controls and indicators to provide users with organized interactive panels.